2016
DOI: 10.1515/hukin-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oxygen uptake during and after the execution of resistance exercises and exercises performed on ergometers, matched for intensity

Abstract: The aim of this study was to compare the values of oxygen uptake (VO2) during and after strength training exercises (STe) and ergometer exercises (Ee), matched for intensity and exercise time. Eight men (24 ± 2.33 years) performed upper and lower body cycling Ee at the individual’s ventilatory threshold (VE/VCO2). The STe session included half squats and the bench press which were performed with a load at the individual blood lactate concentration of 4 mmol/l. Both sessions lasted 30 minutes, alternating 50 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…Overall results indicated that, for the physiological variables examined, responses to resistance training or ‘cardio’ exercise modalities are similar when effort and duration are matched, supporting previous speculation ( Fisher & Steele, 2014 ). This has been reported previously for low effort, duration matched exercise approaches ( Vilaca-Alves et al, 2016 ; Kuznetsov et al, 2011 ). However, our study would appear to be the first to examine ecologically valid high intensity of effort exercise.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall results indicated that, for the physiological variables examined, responses to resistance training or ‘cardio’ exercise modalities are similar when effort and duration are matched, supporting previous speculation ( Fisher & Steele, 2014 ). This has been reported previously for low effort, duration matched exercise approaches ( Vilaca-Alves et al, 2016 ; Kuznetsov et al, 2011 ). However, our study would appear to be the first to examine ecologically valid high intensity of effort exercise.…”
Section: Discussionsupporting
confidence: 86%
“…For example, it is thought that, similarly to ‘cardio’ modalities, resistance training to a high intensity of effort results in maximal aerobic and anaerobic metabolism, and as such local working muscle oxygen utilisation (VO 2 ) and lactate production ( Steele et al, 2012 ). Indeed, when matched for physiological effort (at the load/power eliciting individual ventilatory threshold/onset of blood lactate accumulation at 4 mmol L −1 ), resistance training modalities (half squats and bench press) have been shown to elicit similar acute VO 2 to ‘cardio’ modality exercise (lower and upper body cycling ( Vilaca-Alves et al, 2016 ). Further, high effort resistance training increases muscle water content ( Giessing et al, 2016 ; Ribiero et al, 2014 ) resulting in muscle swelling that appears to be largely independent of external load ( Loenneke et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall results indicated that, for the physiological variables examined, responses to resistance training or 'cardio' exercise modalities are similar when effort and duration are matched, supporting previous speculation (Fisher & Steele, 2014). This has been reported previously for low effort, duration matched exercise approaches (Vilaca-Alves et al, 2016;Kuznetsov et al, 2011). However, our study would appear to be the first to examine ecologically valid high intensity of effort exercise.…”
Section: Discussionsupporting
confidence: 63%
“…Acute studies that have matched conditions by effort and duration have found similar physiological responses between resistance training and 'cardio' modalities Vilaça-Alves et al, 2016). Steele et al (2018) examined the effect of modality upon acute physiological response during high intensity of effort interval based exercises; leg press exercise (4 x 12RM using 2 seconds concentric and 3 seconds eccentric repetition durations thus meaning each set lasted ~ 60 seconds), and cycle ergometry (4x 60 seconds bouts using 6 resistance level permitting 80 -100 rpm but culminating with being unable to sustain the minimum cadence for the final 5 -10 seconds).…”
Section: Introductionmentioning
confidence: 96%